Degrammaticalization in North Saami: Development of adpositions, adverbs and a free lexical noun from inflectional and derivational suffixes - Ylikoski, Jussi (Helmut Buske Verlag, 2016)
Published version available in: Hasselblatt, C., Wagner-Nagy, B. (eds.): Finnisch-Ugrische Mitteilungen 40, 2016. ISBN: 978-3-87548-788-6. Helmut Buske Verlag. This article discusses degrammaticalization in North Saami. Globally, one of the best known examples of degrammaticalization is the development of the North Saami adposition and adverb haga ‘without’ from an earlier abessive case suffix. This article builds on earlier studies by examining haga in greater detail and by relating the development of haga to its cognates dagi and dagá in Lule Saami. The history of the Saami abessive sheds light to the understanding of the North Saami morpheme -naga, a derivational suffix most likely originating from the Proto-Saami essive *-na, which in turn goes back to the Proto-Uralic locative case suffix. It is shown that denominal “contaminative” adjectives such as varranaga ‘stained with blood’ and gáfenaga ‘stained with coffee’ have given rise both to the postposition naga ‘stained with’ and, most importantly, to the noun (-)naga ‘stain’ which mainly occurs in compound nouns such as varranaga(t) ‘blood stain(s)’ and gáfenaga(t) ‘coffee stain(s)’ in the Guovdageaidnu dialect of North Saami. Emergence of a concrete content word such as this appears to be the very first attested example of a degrammaticalization chain going all the way from an affix to a lexical noun.